The journal of Douglas Allen Deeds : the Donner Party expedition - Philbrick, W. R. (W. Rodman) (New York : Scholastic, 2001)
Douglas Deeds, a fifteen-year-old orphan, keeps a journal of his travels by wagon train as a member of the ill-fated Donner Party, which became stranded in the Sierra Nevada mountains in the winter of 1846-47.
920
Accelerated Reader AR
Keywords: Donner Party -- Juvenile fiction; Overland journeys to the Pacific -- Fiction; Survival -- Fiction; Orphans -- Fiction; Diaries -- Fiction